PENGARUH MASSAGE ENDORPHIN TERHADAP KECEMASAN IBU PERIMENOPAUSE - Elfitria.S; Franshisca Sihombing, Sarmauli; Jas, Admar (Universitas Batam, 2025)
Anxiety in menopause is a subjective emotional response and judgment of the individual that is influenced by the subconscious, generally accompanied by autonomic symptoms that last for some time. The anxiety that occurs can be overcome by thinking positively and stimulating happiness hormones to come out. This happiness hormone is one of the endorphin hormones that can provide a relaxing effect, which can stimulate the body to release endorphin compounds that are pain relievers and can create a feeling of comfort. This research instrument uses SOP massage endorphins. The analysis of this study uses the Design used in this study is a Quasi Experimental research using the Posttest Only Control Group Design. The sample selection technique was using Simple Random Sampling. The results of the study showed that there was a decrease in perimenopausal maternal anxiety in the Karimun Health Center Work Area in 2024, where the p value was 0.000 < 0.05. The anxiety level of perimenopausal mothers in the control group had moderate anxiety as many as 22 people (45.83%) and after being given endorphin massage had mild anxiety as many as 25 people (52.08%). It is hoped that the next researcher can continue research on endorphin massage and perimenopausal mothers with different variables and the time of research added. Endorphin Massage, Perimenopausal Maternal Anxiety